Endothelial activation impairs the function of small extracellular vesicles - Herrera-Zelada, Nicolas; Zúñiga-Cuevas, Úrsula; Ramírez-Reyes, Andrés; Norambuena-Soto, Ignacio; Venegas-Zamora, Leslye; Troncoso, Mayarling F.; Hernández, Alejandra; Sánchez, Gina; Pedrozo, Zully; Lavandero, Sergio; Riquelme, Jaime A. (Frontiers in Pharmacology, 2023)
Small extracellular vesicles are nanosized vesicles (30–200 nm) that can ferry proteins, nucleic acids, and lipids between cells and therefore, have significant potential as biomarkers, drug delivery tools or therapeutic agents. SEVs of endothelial origin have been shown to -among other functions-reduce in vitro ischemia/reperfusion (I/R) injury in cardiomyocytes, but whether a pro-inflammatory state of the endothelium impairs the functionality of these SEVs remains to be elucidated. To test this, human umbilical vein endothelial cells cells were treated with TNF-α 10 ng/mL and the expression of the pro-inflammatory parameters VCAM-1, ICAM-1 and eNOS were determined by Western blot. SEVs were isolated from endothelial cells treated with or without TNF-α 10 ng/mL using size exclusion chromatography. The size and concentration of SEVs was measured by Nanoparticle Tracking Analysis. The expression of the surface marker CD81 was determined by immunoassay, whereas their morphology was assessed by electron microscopy. The function of endothelial SEVs was assessed by evaluating their cardioprotective effect in an ex vivo model of global I/R using isolated hearts from adult C57BL/6 mice. Treatment of HUVECs with TNF-α induced the expression of VCAM-1 and ICAM-1, whereas eNOS levels were decreased. TNF-α did not affect the production, size, morphology, or expression of CD81. SEVs significantly reduced the infarct size as compared with untreated mice hearts, but SEVs isolated from TNF-α treated cells were unable to achieve this effect. Therefore, a pro-inflammatory state induced by TNF-α does not alter the production of endothelial SEVs but impairs their function in the setting of I/R injury.